The discontent cartel member and cartel collapse: The case of the German cement cartel - Joseph E. Harrington; Kai Hüschelrath; Ulrich Laitenberger; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We hypothesize a particular source of cartel instability and explore its relevance to understanding cartel dynamics. The cartel instability is rooted in the observation that, upon cartel formation, the relative positions of firms are often fixed which may lead some growthconscious members to be discontent. This incongruity between a cartel member's allocated market share and its desired market share may result in systematic deviations and the eventual collapse of the cartel. This hypothesis is then taken to the German cement cartel of 1991-2002. We argue that Readymix was such a discontent cartel member and, using a rich pricing data set, are able to characterize how Readymix deviated, how other firms responded, and how it led to the collapse of the cartel.
Keywords: L41; K21; 330; collusion; cartel; antitrust enforcement; cement